A plastidic ATP/ADP transporter gene, IbAATP, increases starch and amylose contents and alters starch structure in transgenic sweetpotato - Yan-nan WANG; Yan LI; Huan ZHANG; Hong ZHAI; Qing-chang LIU; Shao-zhen HE (Journal of Integrative Agriculture, 2016)
A plastidic adenosine triphosphate (ATP)/adenosine diphosphate (ADP) transporter (AATP) is responsible for importing ATP from the cytosol into plastids. In dicotyledonous plants, increasing ATP supply is a potential way to facilitate anabolic synthesis in heterotrophic plastids. In this study, a gene encoding the AATP protein, named IbAATP, was isolated from sweetpotato (Ipomoea batatas (L.) Lam.). Transcripts of IbAATP were predominantly detected in the storage roots and leaves and were induced by exogenous sucrose and subjected to circadian rhythm. Transient expression of IbAATP in tobacco and onion epidermal cells revealed the plastidic localization of IbAATP. The overexpression of IbAATP in sweetpotato significantly increased the starch and amylose contents and led to enlarged starch granules. The IbAATP-overexpressing plants showed altered fine structure of amylopectin, which contained an increased proportion of chains with a degree of polymerization (DP) of 10–23 and a reduced number of chains with a DP of 5–9 and 24–40. In addition, starch from the transgenic plants exhibited different pasting properties. The transcript levels of starch biosynthetic genes, including IbAGP, IbGBSSI, IbSSI-IV, and IbSBE, were differentially regulated in the transgenic plants. These results revealed the explicit role of IbAATP in the starch biosynthesis of sweetpotato and indicated that this gene has the potential to be used to improve starch content and quality in sweetpotato and other plants.